2013
DOI: 10.1186/1471-2334-13-344
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the outcome of healthcare-associated and community-acquired bacteramia: a prospective cohort study

Abstract: BackgroundHealthcare-associated (HCA) bloodstream infections (BSI) have been associated with worse outcomes, in terms of higher frequencies of antibiotic-resistant microorganisms and inappropriate therapy than strict community-acquired (CA) BSI. Recent changes in the epidemiology of community (CO)-BSI and treatment protocols may have modified this association. The objective of this study was to analyse the etiology, therapy and outcomes for CA and HCA BSI in our area.MethodsA prospective multicentre cohort inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…Bloodstream infections are common both in the community (3)(4)(5) and in the hospital (6)(7)(8)(9). Escherichia coli is a major overall causative organism found in community-acquired and hospital-acquired bloodstream infections (3,10). Alarmingly, Gram-negative bacteria are rapidly developing resistance to broadspectrum antibiotics and, in some circumstances, have become panantibiotic-resistant (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Bloodstream infections are common both in the community (3)(4)(5) and in the hospital (6)(7)(8)(9). Escherichia coli is a major overall causative organism found in community-acquired and hospital-acquired bloodstream infections (3,10). Alarmingly, Gram-negative bacteria are rapidly developing resistance to broadspectrum antibiotics and, in some circumstances, have become panantibiotic-resistant (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have investigated bacteremia of unknown origin (BUO) [8] despite its frequent occurrence at an estimated 8-22% of bacteremia cases [9][10][11]. Studies have pointed towards increased mortality when the origin of bacteremia is unknown/undetermined [12][13][14], underlining the importance of locating the primary site of infection in BUO.…”
Section: Introductionmentioning
confidence: 99%
“…Retamar et al examined 341 episodes of community-onset bloodstream infections, and they found that 6.3% were caused by MDR isolates, from which 3.8% were ESBL producers. Again, MRSA was not reported as a causative agent [28]. However, we note that some authors document MDR organisms as possible etiologies at higher rates, but these results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 61%